Effect of a Lipid-Based Nutrient Supplement on Insulin-like Growth Factor-1 Level (IGF-1) in 6-12 Month-old Children in South Central Timor of the East Nusa Tenggara Province - Rantesalu, Matius (Pakistan Journal of Nutrition, 2017)
Objective: This study aimed to assess the effect of a lipid-based nutrient supplement (LNS) on the levels of insulin-like growth factor-1 (IGF-1) in 6-12 month-old children in South Central Timor, East Nusa Tenggara province. Materials and Methods: This study used a quasi-experimental design that was carried out in 9 districts of South Central Timor. The samples were divided into the LNS group (n = 24), the MP-ASI SUN (Breast feeding supplementary food group) (n = 24) and the control group (n = 24). Examination of IGF-1 was conducted by the ELISA method, followed by 3 months LNS intervention. Results: The results showed that the factors associated with the level of IGF-1 were consumption of protein (p = 0.002), zinc (p = 0.013), phosphorus (p = 0.000), family income (p = 0.023) and length of the breast feeding period (p = 0.000). The median IGF-1 level before the intervention in the LNS group was -0.004 ng mL–1 and the median IGF-1 level after the intervention was 3.75. Before the intervention, the median IGF-1 in the MP-ASI group was 0.005 and the median IGF-1 level was 0.21 ng mL–1 after the intervention. In the control group, the median IGF-1 level before the intervention was -0.005 and the median IGF-1 level after the intervention was -1.48 ng mL–1. Conclusion: There were differences in the levels of IGF-1 after the intervention between the LNS and control groups (p = 0.000, p